Borrowings or Code-Switching? Analysis of Ways of Morphosyntactic Integration of Lithuanian and Russian Nouns in the Novel "Robczik" by Bartosz Połoński - Masojć, Irena (Slavistica Vilnensis, 2023)
One of the most debated issues in the research on linguistic interactions includes the problem of differentiating between loan words and effects of code-switching, which is solved in a particularly complex way by studying the interaction of closely related languages.  The aim of the article is to reveal various ways of integrating Lithuanian and Russian nouns used in informal communication in the Polish language in Lithuania and to make attempts to answer the question of whether the degree of morphosyntactic adaptation can be used to determine the boundary between the loan words and effects of code-switching. The study is based on the linguistic material of the novel Robczik by Bartosz Połoński, in which the author fairly accurately reconstructed the slang of young people at the end of the 20th and the beginning of the 21st centuries. The analysis shows that in the case of typologically and genetically similar languages, foreign lexical items are incorporated into the syntactic structure of the language in several ways. However, the morphosyntactic integration of Lithuanian and Russian words is not a sufficient criterion to distinguish the phenomenon of borrowing from that of code-switching. Other criteria, such as phonological, which can only be applied to spoken linguistic material, may be of utmost importance.
Keywords: Polish slang in Lithuania; Bartosz Połoński; borrowings; code-switching; morphological integration; syntactic integration